The Contribution of the Self-adjusting File in Debris Removal in Root Canal Retreatment: A Systematic Review and Meta-analysis of in Vitro Studies - El Abbassi, Salma; Sakout, Majid (Iranian Endodontic Journal, 2026)
Introduction: To assess the benefit of the adjunctive use of the Self-adjusting File (SAF) system as a final step in root canal retreatment for the removal of residual filling material. Materials and Methods: A systematic review of in vitro studies was conducted on extracted mature permanent teeth undergoing endodontic retreatment, comparing residual canal debris before and after supplementary use of the SAF system. The electronic search was performed across nine databases: MEDLINE (via PubMed), the Cochrane Library, Scopus, EBSCOhost, Elsevier, ScienceDirect, Web of Science, LILACS, and Google Scholar. Data from the included studies were extracted and analyzed, and key findings were summarized alongside a risk of bias assessment. A random-effects meta-analysis was performed using Hedges’ g as the effect size measure. Studies were stratified into three subgroups according to canal morphology: oval-shaped, curved mesial, and severely curved canals. All statistical analyses were conducted in JASP software using restricted maximum likelihood (REML) estimation. Results: From an initial pool of 517 identified records, 16 studies met the inclusion criteria. No retreatment method achieved complete debridement of the root canal system. Nevertheless, the adjunctive use of the SAF system significantly improved debris removal in eight of the included studies. Conclusion: The adjunctive use of the SAF system following root canal filling removal improves canal cleanliness in anatomically challenging canals, particularly oval-shaped and severely curved configurations. However, the available evidence remains insufficient to support its routine clinical application, and its use should be guided by root canal morphology.